12(v+3)-3v=(3v+4)-19

Simple and best practice solution for 12(v+3)-3v=(3v+4)-19 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12(v+3)-3v=(3v+4)-19 equation:


Simplifying
12(v + 3) + -3v = (3v + 4) + -19

Reorder the terms:
12(3 + v) + -3v = (3v + 4) + -19
(3 * 12 + v * 12) + -3v = (3v + 4) + -19
(36 + 12v) + -3v = (3v + 4) + -19

Combine like terms: 12v + -3v = 9v
36 + 9v = (3v + 4) + -19

Reorder the terms:
36 + 9v = (4 + 3v) + -19

Remove parenthesis around (4 + 3v)
36 + 9v = 4 + 3v + -19

Reorder the terms:
36 + 9v = 4 + -19 + 3v

Combine like terms: 4 + -19 = -15
36 + 9v = -15 + 3v

Solving
36 + 9v = -15 + 3v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-3v' to each side of the equation.
36 + 9v + -3v = -15 + 3v + -3v

Combine like terms: 9v + -3v = 6v
36 + 6v = -15 + 3v + -3v

Combine like terms: 3v + -3v = 0
36 + 6v = -15 + 0
36 + 6v = -15

Add '-36' to each side of the equation.
36 + -36 + 6v = -15 + -36

Combine like terms: 36 + -36 = 0
0 + 6v = -15 + -36
6v = -15 + -36

Combine like terms: -15 + -36 = -51
6v = -51

Divide each side by '6'.
v = -8.5

Simplifying
v = -8.5

See similar equations:

| 9(x+5)=3(3x+1)+42 | | 175000+550x=300440 | | (-8x+3)+(-5x)+x=7-12x | | 4b-b^2=0 | | 5+x/10-x=1/2 | | 0.18(24)+0.03=0.09(12+x) | | 3j+2k+2j-3k= | | 2=15x+4.9x^2 | | 6x^3+4x^2=2x | | -(-14a-17b)= | | x+3x/2=25 | | 3n-2=5n-12 | | 4n=-244 | | x(x^2+6x+12)=42 | | 9x/2-4=50 | | 63x^3-35x^2+36x-20=0 | | 7X(X-2)+13(X-3)=-3 | | 11-y=291 | | (5/x-1)-(2-2x/x) | | x-5.5=40.8 | | (4z+6)(4+z)=0 | | 2x+6-4(x+1)=3x+6 | | y=-0.0665x^2+3.58x+122 | | 195x/100-x | | 151.61=2.48w+15.47 | | 7385-67x=5509 | | x-5.5=57.6 | | 3k+7=5k-5 | | 5x^6+8x^3= | | 6b-8=4-3b | | 9.8x=102.9 | | i=100*0.12*2 |

Equations solver categories